2010
DOI: 10.1002/pts.893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐pressure food processing on the mass transfer properties of selected packaging materials

Abstract: SUMMARYThe effect of high-pressure processing (HPP) on the total migration into distilled water and olive oil and on the barrier properties of four complex packaging materials were evaluated. The fi lms were polyethylene/ ethylene-vinyl-alcohol/polyethylene (PE/EVOH/PE), metallized polyester/polyethylene, polyester/polyethylene (PET/PE), and polypropylene-SiOx (PPSiOx). Pouches made from these fi lms were fi lled with food simulants, sealed and then processed at a pressure of 400 MPa for 30 min, at 20 or 60°C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 20 publications
(21 reference statements)
0
21
1
2
Order By: Relevance
“…The frustration of accessing packaging has been termed ‘Wrap rage’, and a significant number of studies have questioned, observed and measured people's interaction with packaging in order to gain insights into what makes packaging difficult to open …”
Section: Introductionmentioning
confidence: 99%
“…The frustration of accessing packaging has been termed ‘Wrap rage’, and a significant number of studies have questioned, observed and measured people's interaction with packaging in order to gain insights into what makes packaging difficult to open …”
Section: Introductionmentioning
confidence: 99%
“…Ultra-high-pressure processing increased solubility of N 2 and O 2 in the polypropylene heat-sealing inner layer and voids and pits form if the pressure is rapidly released (Fairclough and Conti, 2009), which might reduce package seal integrity. Polyester/polyethylene film had minimal changes in properties after high-pressure pasteurization compared with polyethylene/ethylene-vinyl-alcohol/ polyethylene, metallized polyester/polyethylene and polypropylene-silicon oxide films (Galotto et al ., 2010). Packaging factors affecting high-pressure efficiency and effectiveness are excessive amounts of packaging, the amount of gas inside the package and the sealing ability of the flexible packaging material.…”
Section: Processing Improvementsmentioning
confidence: 97%
“…Recently, Galotto et al (35) investigated the effect of HPP on the total migration into water (aqueous food simulant) and olive oil (fatty food simulant) from four packaging materials (PE/EVOH/PE, mPET/PE, PET/PE and PP-SiOx). Pouches made from these films were filled with food simulants, sealed, and then processed at a pressure of 400 MPa for 30 min at 20 or 60°C.…”
Section: Global Migrationmentioning
confidence: 99%